Comparative analysis of dental arches stability in patients with cleft lip and palate after rehabilitation treatment - Curvêllo, Victor Prado (2018)
While the maxillary growth and development in patients with cleft lip and palate (PLC) is very studied at early age, the literature lacks studies at adulthood. The study of dental arches after oral rehabilitation with dental prostheses is necessary in this group of patients to verify the stability of the interdisciplinary treatment performed. This study aimed to evaluate the stability of dental arches in adults with cleft lip and palate who received orthodontic treatment and were rehabilitated with dental prostheses compared with adults who received implant-supported prosthesis and conventional fixed partial dentures, both in the area of cleft lip and palate The group rehabilitated with implants was composed of 20 patients (7 males, 13 females; mean age of 25 years) and the group rehabilitated with a conventional fixed partial denture consisted of 15 patients (8 females and 7 males; mean age of 25 years). The dental casts were scanned with a laser scanner in the two proposed treatment phases: T1- immediately after completion of orthodontic treatment and T2- at least 1 year after oral rehabilitation with dental prostheses. The stability evaluation comprised the subtraction of T2 from T1 measurements ( = T2-T1). All linear, inter-canine, inter-molar and total arch length measurements were performed digitally. The independent t-test compared the groups between the times (p0.05). Among groups, the stability comparison showed statistically differences in inter-canine measurements, but non-significant differences in inter-molar distance and total arch length. Adults with cleft lip and palate rehabilitated with fixed partial and implant-supported dentures had a difference in dental arch stability. Fixed partial prosthesis provided a greater linear dimensional stability of dental arches in this group of individuals